PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPATU PADA CV YUANGZI SHOES DI KOTA BUMI TANGERANG - Maimunah; Purwanti (Jurnal Nusa Manajemen, 2025)
The purpose of this study is to determine the influence between Price and Product Quality on Shoe Purchase Decisions at CV Yuangzi Shoes in Kota Bumi Tangerang, both partially and simultaneously. This research method uses a descriptive quantitative method with a sample of 94 respondents, the data analysis techniques used are: validity test, reality test, normality test, multicomality test, autocorrelation test, heteroscedasticity test, simple linear regression test, multiple linear regression test, simple correlation coefficient test, multiple correlation coefficient test, determination coefficient analysis test, t test and f test. Based on the results of the t-test, the t-count value is 20.831 > 1.662 and the significance value for the Price variable (X1) is 0.000, the significant value is smaller than the probability value of 0.05 or 0.000<0.05, meaning that the Price variable has a positive and significant effect on the Purchase Decision variable (Y). Based on the results of the t-test, the t-count value is 5.441 > 1.662 and the significance value for the Product Quality variable (X2) is 0.000, the significance value is smaller than probability value 0.05 or 0.000 < 0.05, meaning that the Product Quality variable has a positive and significant effect on the employee performance variable (Y). Based on the results of the f test, the results show that the Price (X1) and Product Quality (X2) variables simultaneously have a significant effect on the Purchase Decision (Y) as evidenced by the value of the f coefficient of 1921.105 > 3.095 with a significance value of 0.000 < 0.05. It can be concluded that Price (X1) and Product Quality (X2) simultaneously have a positive and significant influence on Purchase Decision (Y).